2019
DOI: 10.18203/issn.2455-4510.intjresorthop20190798
|View full text |Cite
|
Sign up to set email alerts
|

A non-interventional, prospective, multicentric real life Indian study to assess safety and effectiveness of un-denatured type 2 collagen in management of osteoarthritis

Abstract: <p class="abstract"><strong>Background:</strong> Osteoarthritis (OA) is the most common musculoskeletal conditions affecting the quality of life. Undenatured collagen type II has emerged as one of the promising treatment options in treatment of OA. Despite being available in India, clinical safety and efficacy have not been evaluated. We performed a non-interventional, real-life study to determine its safety and efficacy in Indian population.</p><p class="abstract"><strong>M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
0
8
0
1
Order By: Relevance
“…Placebo Oral/2 capsules (1 g) of BCC, 2 times daily 1 capsule = 300 mg hydrolyzed collagen type II + 100 mg CS + 50 mg HA Chicken/∼1.5 − 2.5 kDa Stančík (2012) [ 68 ] Slovakia RCT (double-blind) Knee OA patients Undenatured type I collagen (COL-I) vs. Placebo Oral/1 × 8 mg pure lyophilized collagen type I in capsule Bovine/NA Trč (2011) [ 69 ] Czech Republic RCT (double-blind) Knee OA patients Enzymatic hydrolyzed collagen vs. glucosamine sulphate Oral/10 g, once daily NA/NA Observational studies Azeem (2019) [ 70 ] India Open-label observational study Knee OA patients UC-II (undenatured type II collagen)/no control Oral/daily capsule of 40 g of UC-II Obtained from chicken sternum/NA De Luca (2019) [ 71 ] Italy Retrospective study Knee OA patients An injectable collagen formulation consisting of bovine hydrolyzed type I collagen (ChondroGrid) / No control Intra-articular injection/ Three 2 ml (4 mg) CG injections, the first two 15 days apart, and the third one 30 days after the second Bovine/ < 3 kDa Kilinc (2018) [ 72 ] Turkey Prospective, single-center, open-label study (observational) Grade 2 to 3 K-L grade knee OA patients Promerim (hydrolyzed fish collagen) / No control Oral/720-mg Promerim for the first 15 days after admission, and then 360 mg for the second 15 days Fish/NA Mehra (2019) [ 73 ] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Placebo Oral/2 capsules (1 g) of BCC, 2 times daily 1 capsule = 300 mg hydrolyzed collagen type II + 100 mg CS + 50 mg HA Chicken/∼1.5 − 2.5 kDa Stančík (2012) [ 68 ] Slovakia RCT (double-blind) Knee OA patients Undenatured type I collagen (COL-I) vs. Placebo Oral/1 × 8 mg pure lyophilized collagen type I in capsule Bovine/NA Trč (2011) [ 69 ] Czech Republic RCT (double-blind) Knee OA patients Enzymatic hydrolyzed collagen vs. glucosamine sulphate Oral/10 g, once daily NA/NA Observational studies Azeem (2019) [ 70 ] India Open-label observational study Knee OA patients UC-II (undenatured type II collagen)/no control Oral/daily capsule of 40 g of UC-II Obtained from chicken sternum/NA De Luca (2019) [ 71 ] Italy Retrospective study Knee OA patients An injectable collagen formulation consisting of bovine hydrolyzed type I collagen (ChondroGrid) / No control Intra-articular injection/ Three 2 ml (4 mg) CG injections, the first two 15 days apart, and the third one 30 days after the second Bovine/ < 3 kDa Kilinc (2018) [ 72 ] Turkey Prospective, single-center, open-label study (observational) Grade 2 to 3 K-L grade knee OA patients Promerim (hydrolyzed fish collagen) / No control Oral/720-mg Promerim for the first 15 days after admission, and then 360 mg for the second 15 days Fish/NA Mehra (2019) [ 73 ] …”
Section: Resultsmentioning
confidence: 99%
“…In addition, it also has a very good safety profile NA Trč (2011) [ 69 ] Colatech ® (NA) NA 3 months Colatech ® : 47 GS: 46 Colatech ® has demonstrated to be efficient in improving clinical status in knee OA (KOA) patients, with significant improvement in pain scores, functional joint status and a better quality of life. It demonstrated clinically better efficacy than GS after 2, 4, 8, and 12 weeks of treatment NA Observational studies Azeem (2019) [ 70 ] UC-II ® (NA) NA 120 days 100 This study showed that UC-II, a food ingredient containing type II undenatured collagen, significantly improved knee function in a patient with OA knee joint after 120 days of observation Until we conduct longer tests, it remains an open question whether a slow-acting additive, such as UC-II, can affect the biomechanical condition of the knee with OA sufficient to improve the knee’s ROM (knee flexion range) De Luca (2019) [ 71 ] ChondroGrid (CG), (Bioteck, Arcugnano, Italy) NA 6 months 20 patients Results of the present study (…) indicate (that) CG may be a safe and effective adjuvant in the treatment of symptomatic knee OA by intra-articular injection The overall results are extremely promising and highlight the need for further controlled prospective studies to investigate the full extent of the beneficial effects of CG treatment and whether intra-articular CG injection may be more beneficial than other non-pharmacological treatments already available in the clinical practice Kilinc (2018) [ 72 ] NA (NA) No financial support received 1 month 92 patients The results of this single-center, open-label clinical study demonstrate that Promerim is a viable natural treatment option for treating knee OA NA Mehra (2019) [ 73 ] DUPACT ® (Wockhardt...…”
Section: Resultsmentioning
confidence: 99%
“…Up to date, several clinical trials regarding the use of collagen as a food supplement for joint health have been published. Most of the studies have evaluated the therapeutic potential of either native type II collagen [ 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ] or hydrolyzed collagens [ 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ] in patients with OA. However, both types of collagens have been also tested in non-osteoarthritic individuals suffering joint discomfort [ 108 , 109 , 110 , 111 , 112 , 113 ].…”
Section: Clinical Evidencementioning
confidence: 99%
“…На сегодняшний день проведено несколько клинических исследований эффективности и безопасности применения коллагена в качестве фармаконутрицевтика для поддержания здоровья суставов у пациентов с ОА. В большинстве исследований оценивали терапевтический потенциал нативного CII [92][93][94][95][96][97] или гидролизованного коллагена [98][99][100][101] у пациентов с ОА. Оба типа коллагена были протестированы у лиц, страдающих от дискомфорта в суставах при отсутствии ОА [102][103][104].…”
Section: механизм действия и перспективы примененияunclassified